Synthesis and X-Ray Crystal Structure of α-Keggin-Type Aluminum-Substituted Polyoxotungstate - Kato, Chika Nozaki; Makino, Yuki; Yamasaki, Mikio; Kataoka, Yusuke; Kitagawa, Yasutaka; Okumura, Mitsutaka (IntechOpen, 2012)
None